La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 596/2017 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2017)
Ejemplar: Revista de la ESG. Año 94, no. 596 (may-ago 2017). 94 p.